Training methods for high-altitude acclimatization and its applications in military - WANG Yongchun; LI Jiaxiang (陆军军医大学学报)
The unique geography， climate， and natural conditions of plateaus pose significant challenges to the physical health and combat effectiveness of stationed troops. In high-altitude regions， maladaptation can lead to acute mountain sickness， such as high-altitude pulmonary edema and high-altitude cerebral edema. Previous studies have shown that gradual acclimatization is an effective strategy for preventing and mitigating altitude sickness. Additionally， non-pharmacological strategies such as intermittent hypoxia and pre-simulated altitude training have also been proven to effectively promote altitude acclimatization. Conventional acclimatization strategies take longer time and are not conducive to rapid deployment of military personnel. In this article， we review various acclimatization training for individuals entering high-altitude areas， in order to provide a reference for the research and application of scientific and efficient altitude acclimatization training strategies.